Twisted aromatic backbone engineering enables high-performance anion exchange membranes for durable water electrolysis - Wenjing Li; Jinsheng Li; Pingxia Zhang; Wei Qi; Xue Wang; Feiyan An; Youze Zeng; Dong Pan; Rina Sa; Meiling Xiao; Wei Xing; Jianbing Zhu; et al. (Chemical Engineering Journal, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Assessment of Spirulina Residue Meal as a Substitute for Fish Meal in Juvenile Rainbow Trout (Oncorhynchus mykiss) Diets: Impact on Growth, Antioxidative Capacity, Carcass Composition and Hepatointestinal Health - Ning Fu; Yuyu Wang; Shengwen Niu; Mengxin Xing; Meiling An; Lu Zhao; Gefeng Xu; Hairui Yu; Jiubo Cui (Fishes, 2026)
A 7-week study was conducted to investigate the effects of replacing fish meal (FM) with Spirulina residue meal (SPRM) on the growth, feed utilization, carcass composition, antioxidant ability, liver and intestinal histology of juvenile rainbow trout (Oncorhynchus mykiss) (initial body weight 5.36 ± 0.04 g). Four isonitrogenous (42%) and isolipidic (16%) diets were formulated to replace FM protein with SPRM at 0 (SPRM0), 10% (SPRM10), 20% (SPRM20) and 30% (SPRM30), respectively. Results showed that growth, feed utilization, carcass amino acid profile, serum biochemical indices, antioxidant ability, intestinal and liver histology were not significantly affected by dietary SPRM levels. Whole-body lipid content decreased as dietary SPRM replacement levels increased, and fish fed diet SPRM30 had lower lipid content than that fish fed diet SPRM0 (p 0.05). The muscle C22:6n-3 (DHA) content decreased, but C18:3n-6 and n-6/n-3 polyunsaturated fatty acid (PUFA) ratio increased with increasing SPRM levels, and fish fed diet SPRM30 had significantly lower DHA content and higher n-6/n-3 ratio than the group fed SPRM0 (p 0.05), but higher than the SPRM10 and SPRM20 groups (p

Novel stomach-predominant C-type lectin (LvnCTL) triggers immune response against Vibrio parahaemolyticus and WSSV in shrimp Litopenaeus vannamei - Shengwen Niu; Ning Fu; Yuyu Wang; Mengxin Xing; Meiling An; Hongli Xu; Bang Xiao; Weiyan Song; Yongqing Zeng; Orlando Borras-Hidalgo; Hui Wang (Fish & Shellfish Immunology, 2026)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Facile solvothermal synthesis of ultrafine platinum nanowires on carbon nanotubes to enhance hydrogen evolution performance - Chang-An Zhou; Meiling Ran; Huixi Chen; Tingting Ma; Chunhui Wu; Hong Zhang; Lei Song; Chao Wang; Kui Ma; Hairong Yue (Fuel, 2025)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Source appointment of δ13C in sediments of a maar lake in southern China: Implications of fossil fuel CO2 emissions - Meiling Guo; Yongming Han; Weiguo Liu; Yunning Cao; Dewen Lei; Weijian Zhou; Zhisheng An (Applied Geochemistry, 2024)

Utilizing different types of biomass materials to modify steel slag for the preparation of composite materials used in the adsorption and solidification of Pb in solutions and soil - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Fanmin Zhu; Zhanbin Huang (Science of The Total Environment, 2024)

A halogen-free hyper-crosslinked ionic polymer for efficient multi-conversion of CO2 into carbonates under mild conditions, with a combination of theoretical study - Bowen Jiang; Jia Liu; Wenjie Xiong; Meiling Weng; Jigang An; Yuewei Fan; Leizhi Zheng; Guoqiang Yang; Zhibing Zhang (Chemical Engineering Journal, 2023)

Experimental and mechanistic study on the removal of lead from solution by sulfuric acid modified steel slag adsorbent - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Zhanbin Huang (Journal of Environmental Chemical Engineering, 2023)

Molecular cloning and expression analysis of major intrinsic protein gene in Chlamydomonas sp. ICE-L from Antarctica - Lulu Li; Meiling An; Changfeng Qu; Zhou Zheng; Yibin Wang; Fangming Liu; Yingying He; Xiaodong He; Jinlai Miao (Extremophiles, 2017)

Biomass, nutrient uptake and fatty acid composition of Chlamydomonas sp. ICE-L in response to different nitrogen sources - Meiling An; Yibin Wang; Fangming Liu; Xiaoqing Qi; Zhou Zheng; Naihao Ye; Chengjun Sun; Jinlai Miao (Acta Oceanologica Sinica, 2017)

Analysis of ΔpH and the xanthophyll cycle in NPQ of the Antarctic sea ice alga Chlamydomonas sp. ICE-L - Shanli Mou; Xiaowen Zhang; Naihao Ye; Jinlai Miao; Shaona Cao; Dong Xu; Xiao Fan; Meiling An (Extremophiles, 2013)